Leukotriene A4 hydrolase: protection from mechanism-based inactivation by mutation of tyrosine-378. - Mueller, M; Blomster, M; Oppermann, U; Jörnvall, H; Samuelsson, B; Haeggström, J (1996)
Leukotriene A4 (LTA4) hydrolase [(7E,9E,11Z,14Z)-(5S,6S)-5,6-epoxyicosa-7, 9,11,14-tetraenoate hydrolase; EC 3.3.2.6] is a bifunctional zinc metalloenzyme that catalyzes the final step in the biosynthesis of the potent chemotactic agent leukotriene B4 (LTB4). LTA4 hydrolase/aminopeptidase is suicide inactivated during catalysis via an apparently mechanism-based irreversible binding of LTA4 to the protein in a 1:1 stoichiometry. Previously, we have identified a henicosapeptide, encompassing residues Leu-365 to Lys-385 in human LTA4 hydrolase, which contains a site involved in the covalent binding of LTA4 to the native enzyme. To investigate the role of Tyr-378, a potential candidate for this binding site, we exchanged Tyr for Phe or Gln in two separate mutants. In addition, each of two adjacent and potentially reactive residues, Ser-379 and Ser-380, were exchanged for Ala. The mutated enzymes were expressed as (His)6-tagged fusion proteins in Escherichia coli, purified to apparent homogeneity, and characterized. Enzyme activity determinations and differential peptide mapping, before and after repeated exposure to LTA4, revealed that wild-type enzyme and the mutants [S379A] and [S380A]LTA4hydrolase were equally susceptible to suicide inactivation whereas the mutants in position 378 were no longer inactivated or covalently modified by LTA4. Furthermore, in [Y378F]LTA4 hydrolase, the value of kcat for epoxide hydrolysis was increased 2.5-fold over that of the wild-type enzyme. Thus, by a single-point mutation in LTA4 hydrolase, catalysis and covalent modification/inactivation have been dissociated, yielding an enzyme with increased turnover and resistance to mechanism-based inactivation.